LITERATURE REVIEW: Effectiveness of Chatbot to Reduce the Risk of Coronary Heart Disease using Android-based application - Agnes Atmadjaja; Minarni Watinin; Stefani Nurhadi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: An innovative approach in the form of a discussion platform designed to help users deal with health issues related to coronary artery disease. Chatbot platforms allow the collection of users' data, which is analyzed through natural language processing and behavioral analysis, to provide each user with a customized solution based on their current situation. The data collected and analyzed is accessible. The platform is developed using chatbot technology. Users can interact with chatbots to generate personal chat data stored on the platform. Conflicting information and sensitivity to Coronary Heart Disease (CHD) issues hinder effective communication. Recent technological solutions to maintain weight loss are limited. A chatbot would be suitable to support weight loss as it requires no human intervention, is available 24 hours a day, and supports natural communication while maintaining anonymity. The health system needs an effective and low-cost way to provide optimal health outcomes using conversation-enabled Artificial Intelligence (AI). Humans can interact well with this AI in the form of a fully automated and self-contained text-based mobile tutoring service. CHD is a serious health problem worldwide with multiple and interrelated causes. At the same time, chatbots are becoming more popular for interacting with users in mobile health apps.Objective: We evaluated an Android application. Its main goal is to prevent lifestyle-related diseases that are a risk for CHD, which has been considered at risk for multiple coronary artery disease (CAD), with the overarching goal of gaining compassion through mobile health improvements. The insights gained in this preview article will be used to plan future health care systems and to design an AI capable of advanced healthcare, chronic disease prevention, and self-treatment.Results: The Role of Artificial Intelligence in preventing Coronary Heart Disease (CHD) is done through health screenings. The app warns the user to exercise regularly and maintain food intake by reducing foods high in calories and adding foods high in fiber. Conclusion: Usage of AI in healthcare is associated with CHD prevention, which alters healthy lifestyles. It can also encourage a change in attitude, a high level of user concern for health, and obtain complete health information. Research on artificial intelligence and its use in telemedicine needs to be continued, with clinical trials examining the impact on blood pressure, body mass index, smoking, diabetes mellitus, and user engagement and feedback.